SLAMF8 promotes the proliferation and migration of synovial fibroblasts by regulating the ERK/MMPs signalling pathway. (4th July 2022) - Liu, Jun; Huang, Ying; Zeng, Jiashun; Chen, Changming; Li, Peiting; Ning, Qiaoyi; Guan, Xianyue; Li, Long
Abstract: Rheumatoid arthritis is troublesome to treat effectively and often requires concomitant long-term treatment. Meanwhile, synovial fibroblasts could induce inflammation response and lead to joint erosion, finally causing progressive joint destruction, disability, and increased mortality. This study focussed on the role of SLAM family member 8 (SLAMF8) in mediating cell function from rheumatoid arthritis synovial fibroblasts stimulated with TNF-α. Cell Counting Kit-8 (CCK-8) and colony-forming unit assay were used to evaluate cell proliferation. SLAMF8 expression was analysed by reverse transcription-quantitative PCR (RT-qPCR) and western blot. Annexin V‐FITC/PI double staining was used to measure the apoptosis rate. The cell migration and invasion in TNF-α-stimulated MH7A (human rheumatoid arthritis synovial cell line) and HFLS-RA cells (human fibroblast-like synoviocytes: rheumatoid arthritis) were tested via wound healing assay and transwell migration assay. In the present study, after TNF-α treatments, the SLAMF8 mRNA and protein expression in both MH7A and HFLS-RA cell lines have a time-dependent increase. The attenuation of SLAMF8 ameliorated TNF-α-induced proliferation, invasion and migration in MH7A and HFLS-RA cells. Simultaneously, when SLAMF8 was silenced, the expression of p-ERK, MMP-1, and MMP-13 was suppressed significantly. In summary, these results indicated that the knockdown of the SLAMF8 significantly attenuated TNF-α-induced proinflammatory responses in MH7A and HFLS-RA cells. Therefore, SLAMF8 exhibits therapeutic potential for the management of inflammation in rheumatoid arthritis.